Air Zamzam sebagai Penangkal Virus Covid-19: Studi Takhrij dan Syarah Hadis - Fauza Zahrotul Aini; Susanti Vera; Dody S. Truna (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the hadith related to Zamzam water. This study uses a qualitative approach by applying the takhrij and syarah hadith methods to analyze contemporary issues. The results of this study found the quality status of the hadith of Zamzam water was assessed as hasan li ghairihi, in the sense of maqbul and ma'mul bih to be practiced. While the syarah of this hadith explains that Zamzam water has many properties, one of which is efficacious as a medicine, however, this Zamzam water can absolutely cure various diseases, especially Covid-19, therefore further research is needed. Likewise, Zamzam water has properties according to the intentions of the person who drinks it. The conclusion of this study is the hadith of the Prophet about Zamzam water as an antidote for various types of diseases.